PENGEMBANGAN MEDIA LEMBAR KERJA SISWA (LKS) UNTUK PEMBELAJARAN MATEMATIKA KELAS IV SD - Gamaliel, Ariesta; Rarasati, Ida Putri; Anindia, Desy (Transpublika Publisher, 2024)
The Indonesian government requires schools to implement the revised 2013 curriculum. The goal is to prepare the younger generation to be creative, innovative and critical. Integrated thematic books are incomplete in math materials, so students have difficulty understanding basic concepts. This research uses research and development methods. The goal is to produce learning media in the form of Student Worksheets (LKS) Square Flat Buildings. Based on the results of the media expert validation, it is known that the developed LKS media for Square Flat Buildings obtained a score of 77%, which means that the product is quite feasible and needs a little revision. Based on the results of the material expert, it is known that the media obtained a score of 75%, which means that the media is said to be feasible without revision. The conclusion of this study is that the media developed by researchers received positive responses from all experts, namely media experts, material experts and linguists. However, there are some notes to use this learning media. The learning media made by researchers are intended to improve the quality of learning so that students are interested and happy to follow the learning process.